The Problem of the Implications of the Execution of the Constitutional Court's Decision as Judicial Making in Realizing Legal Certainty - Amanta, Danang Rizky Fadilla; Aliz Zulis Al Hurni (Universitas Ahmad Dahlan, 2025)
From a normative-legal perspective, decisions of the Constitutional Court are deemed final and binding from the moment they are pronounced in a public plenary session. However, in practice, the implementation of Constitutional Court decisions often sparks controversy within Indonesia's Constitutional System. Building on this, the author is interested in conducting further research on the issues surrounding the execution of Constitutional Court decisions concerning the position of the Constitutional Court as a judicial maker and efforts to optimize the implementation of Constitutional Court decision execution to create legal certainty. This research employs a normative juridical method, which involves correlating library research with relevant legislation to obtain data on the problems in the implementation of Constitutional Court decision execution and solutions to overcome the barriers. The analysis method used is descriptive qualitative. The results of this study indicate that there are factors influencing the implementation of Constitutional Court decisions, including the limited authority of the Constitutional Court, the absence of specialized enforcement agencies, the lack of implementation timeframes, the insufficient consequences for violating decisions, and the potential increase in compliance costs. Efforts to optimize the execution of Constitutional Court decisions to create legal certainty include revising relevant laws to grant greater authority to the Constitutional Court and establishing enforcement units to ensure institutional compliance with Constitutional Court decisions. Keywords: Issues; MK decision execution, Legal Certainty